Study on the Contact Conditions of Powder Metallurgy Gear - Fang Cheng; Li Xinmin (Jixie chuandong, 2017)
With the development of powder metallurgy technology in recent years,the applications of powder metallurgy gear becoming more and more widely. But the porosity structure of material may results in larger gear tooth bending deformation of powder metallurgy gear compared with the traditional material gear. The larger gear tooth bending deformation will influence on the transmission efficiency of powder metallurgy gear and even dynamics. By using gear tooth contact conditions of traditional material gears as reference,the influence of the porosity structure of powder metallurgy material on gear contact conditions is studied. At the meantime,the contact fatigue life of surface densified powder metallurgy gear is analyzed. The reference for further research of powder metallurgical gear is provided.